2006
DOI: 10.1186/1465-9921-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss and obstructive sleep apnoea

Abstract: Background: Complete tooth loss (edentulism) produces anatomical changes that may impair upper airway size and function. The aim of this study was to evaluate whether edentulism favours the occurrence of obstructive sleep apnoea (OSA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 29 publications
7
87
0
14
Order By: Relevance
“…In one of the study 1 done in past on 6 edentulous patients it was observed that retropharyngeal space was reduced from 15mm to 6mm, leading to increased apnea hypopnea events. Later on same results were obtained in another study 3 in which the authors hypothesized that edentulism might act in creating the apnoea condition by modifying anatomy and thereby affecting the functions of the pharyngeal airway and of tongue and may be by favouring inflammatory edema. They concluded that risks of removing denture in edentulous patients should be weighed against risk of upper airway collapse.…”
Section: 2311supporting
confidence: 63%
See 1 more Smart Citation
“…In one of the study 1 done in past on 6 edentulous patients it was observed that retropharyngeal space was reduced from 15mm to 6mm, leading to increased apnea hypopnea events. Later on same results were obtained in another study 3 in which the authors hypothesized that edentulism might act in creating the apnoea condition by modifying anatomy and thereby affecting the functions of the pharyngeal airway and of tongue and may be by favouring inflammatory edema. They concluded that risks of removing denture in edentulous patients should be weighed against risk of upper airway collapse.…”
Section: 2311supporting
confidence: 63%
“…3 Obstructive sleep apnea syndrome (OSAS) is a disorder characterised by repeated obstruction of the upper airway, with consequent episodes of apnea and hypoapnea during sleep, snoring, and day time sleepiness. 4,5 Increased pharyngeal collapsibility is reported to be a common cause of obstructive sleep apnea.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors suggest that denture has a protective role on OSAS onset [24][25][26][27]. Its function is to improve a vertical dimension of occlusion (VDO) increase, a correct tongue position, an upper airway collapse reduction and a mandibular advancement.…”
Section: Discussionmentioning
confidence: 99%
“…8 Erovigni et al (2005) demonstrated that wearing denture induces modifications in the position of the tongue, mandible and pharyngeal airway space which can favor the reduction of apnea episodes. 6 Bucca et al (2006) concluded that edentulism might worsen obstructive sleep apnea, particularly in subjects with no respiratory disturbances sleeping with dentures. Edentulism might act by modifying anatomy and function of the pharyngeal airway and tongue and favoring inflammatory edema.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the advantage of removing dentures during sleep should be weighed against the risk of favoring upper airway collapse. 4 Arisaka et al (2009) concluded that wearing complete dentures during sleep improves the AHI of most edentulous OSA patients. 10 Tsuda et al (2010) found the prevalence of suspected SDB in edentulous subjects was higher than in the general population.…”
Section: Introductionmentioning
confidence: 99%